RESEÑA de : Imízcoz, José María; Chaparro, Álvaro (eds.). Educación, redes y producción de élites en el siglo XVIII. Madrid: Sílex, 2013. - Camacho Domínguez, Adriam (Espacio Tiempo y Forma. Serie IV, Historia Moderna, 2014)
RESEÑA de : Imízcoz, José María; Chaparro, Álvaro (eds.). Educación, redes y producción de élites en el siglo XVIII. Madrid: Sílex, 2013.